Gambaran Kadar Sgot dan Sgpt pada Pasien Tuberkulosis Paru Aktif - Stephanie, Graciela; Maulida Julia Saputri , Maulida Julia Saputri; Suparno Putera Makkadafi , Suparno Putera Makkadafi (Politeknik Baubau, 2024)
Tuberculosis (TB) is a global problem with around half a percent of the world's population infected. The number of TB cases in Samarinda City in 2021 will reach 1,464 cases. TB treatment can damage the liver, and the SGOT and SGPT enzymes are related to liver function. SGPT is more commonly found in the liver, while SGOT is found in the liver, heart, skeletal muscles, kidneys, brain and blood cells. The purpose of this study was to determine the levels of SGOT and SGPT in patients with active pulmonary tuberculosis at the Sidomulyo Health Center in Samarinda. This type of research is a descriptive observational study with 30 samples of pulmonary TB patients who are currently undergoing anti-tuberculosis drug (OAT) treatment. Sampling was carried out using total sampling technique. The variables observed were SGOT and SGPT levels. The results of measurements using spectrophotometry showed that normal AST levels were mostly found in 100% female patients, while abnormal AST levels were mostly found in male patients (53%). The highest normal SGPT levels were found in male patients (100%), while the highest abnormal SGPT levels were found in female patients (27%). The examination results also showed that the adult age group with an age range of 20-59 years had normal SGOT levels (33%) and high normal SGPT levels (96%). It can be concluded that the results of SGOT levels based on sex are abnormal in male patients, whereas based on age the results of abnormal SGOT levels in adult patients. Furthermore, SGPT levels based on sex were abnormal in female patients while based on age SGPT levels were abnormal in adolescent patients.